FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU CORPORATE INTERNET REPORTING DALAM MENDUKUNG TRANSPARANSI KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andri Novius (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
This study aims to examine the effect of Economic Growth, Ownership Structure, Company Size, Age of Listing, and Profitability on companies in implementing Corporate Internet Reporting (CIR). The data used in this study is secondary data in the form of data from various industry companies listed on the Indonesia Stock Exchange. The sample used by 21 companies was chosen by purposive sampling method with the research period from 2013 to 2015. The conclusion obtained is that the Economic Growth variable has a negative effect on the practice of financial reporting through the internet (Corporate Internet Reporting), the Ownership Structure variable does not affect the practice of financial reporting through the internet (Corporate Internet Reporting). Likewise the Age of Listing, and Profitability does not significantly influence the practice of financial reporting via the internet (Corporate Internet Reporting). Only company size variables that significantly influence the practice of financial reporting through the internet (Corporate Internet Reporting).